Morphometry and hemodynamics of coronary artery aneurysms caused by atherosclerosis. (May 2019) - Fan, Tingting; Zhou, Zhen; Fang, Wenxuan; Wang, Wenjing; Xu, Lei; Huo, Yunlong
Abstract: Background and aims: Atherosclerosis is the first etiology of coronary artery aneurysm (CAA). It is, however, challenging to inhibit the development of CAA. The aim of the study is to carry out morphometric and hemodynamic analyses in epicardial coronary arteries of patients with CAAs caused by atherosclerosis. Methods: Various morphometric parameters were obtained from the reconstructed epicardial coronary arterial trees of 61 patients and multiple hemodynamic parameters were determined from the computed flow fields. A two-step analysis method was proposed to enhance the risk assessment of CAAs, i.e., coronary artery bifurcation is the major risk factor for CAA followed by high aneurysm shape index (L/W, where L and W refer to the aneurysm length and maximum diameter, respectively). Results: Patients with CAA covering a bifurcation have the higher occurrence (71% and 55% for L/W ≥ 2 and L/W < 2, respectively) of myocardial ischemia relevant to abnormal hemodynamic parameters in comparison with those with CAA in one vessel (43% and 40% for L/W ≥ 2 and L/W < 2, respectively). Patients with CAA of L/W ≥ 2 covering a bifurcation show the worst hemodynamic environment. Conclusions: Morphometric and hemodynamic studies support the two-step analysis method, which provides a clinical rationale for the noninvasive assessment of CAAs. Highlights: A two-step analysis method is proposed to improve the risk assessment of CAAs due to atherosclerosis. Patients with the CAA covering a bifurcation have the higher occurrence of myocardial ischemia. Patients with the CAA of L/W ≥ 2 covering a bifurcation show the worst hemodynamic environment.